2002
DOI: 10.1097/00006223-200211000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Handheld Technology in Nursing Education

Abstract: Advances in technology must be integrated into curricula. The authors review the process and risks associated with adopting handheld technology and offer suggestions for integrating this technology into nursing curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Another studies conducted on the use of hand held devices to deliver workplace learning demonstrated that regular accessibility means young people can access resources in a way that is both convenient and relevant to them. This in turn translates into increased levels of implementation into work practice [13]. Many researchers found a positive association between the use of SNSs and academic performance of the student users.…”
Section: Academic Benefits Of Social Networking Sitesmentioning
confidence: 99%
“…Another studies conducted on the use of hand held devices to deliver workplace learning demonstrated that regular accessibility means young people can access resources in a way that is both convenient and relevant to them. This in turn translates into increased levels of implementation into work practice [13]. Many researchers found a positive association between the use of SNSs and academic performance of the student users.…”
Section: Academic Benefits Of Social Networking Sitesmentioning
confidence: 99%
“…This finding confirms reports that one of the best benefits of using PDAs in clinical settings is as a portable drug reference for instant data retrieval. 2,18,37,38 The other factor, user support, was related to reporting PDA problems and obtaining support from the IS department. Although problems could be reported anytime, as shown by the positive average score of 2.77, support was not available, as revealed by the negative average score of 2.43 and comments.…”
Section: Discussionmentioning
confidence: 99%
“…Tutors can explain that by using a PDA that has relevant electronic resources uploaded onto it, nurses will find answers in their hands, not at the nurses' station. It can be explained that PDAs can bring benefits such as increased productivity, reduced errors, better patient care, and increased worker satisfaction (Huffstutler et al, 2002). All nurses need to network with other nurses to share information, to assist in research, provide and receive mentoring, emotional support, and friendship.…”
Section: Change Managementmentioning
confidence: 99%
“…There have been accounts of how various institutions have used PDAs, for example, Huffstutler (2002). While university libraries have been known to provide information and support to students who use PDAs, many health care programs making use of PDAs seek help from institutional information technology department instead (Young, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation